Peran Hukum Bisnis Dalam Mendorong Inovasi Umkm Di Kota Medan - Silalahi, Lusni; Sannya Arta Sagala; Hanna May Sinaga; Toman Sony Tambunan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Business law plays a crucial role in providing protection and support for Micro, Small, and Medium Enterprises (MSMEs), the backbone of Medan's economy. This qualitative research examines the role of business law in fostering MSME innovation in Medan, addressing a gap in previous research regarding the direct relationship between legal regulations and the innovation process. A literature review found that business law, specifically business legality and the existence and protection of Intellectual Property Rights (IPR), significantly enhances MSME innovation and competitiveness. Despite constraints such as limited capital and infrastructure, business law has been shown to have a positive impact and support MSME creativity. Therefore, the research recommends strengthening competition oversight, facilitating access to financing and licensing, and improving infrastructure and entrepreneurship training to optimize the role of business law in the MSME innovation ecosystem.